Does the surgical waiting list affect pathological and survival outcome in resectable pancreatic ductal adenocarcinoma?. Issue 5 (May 2018) - Marchegiani, Giovanni; Andrianello, Stefano; Perri, Giampaolo; Secchettin, Erica; Maggino, Laura; Malleo, Giuseppe; Bassi, Claudio; Salvia, Roberto
Abstract: Background: High-volume centers have to deal with long surgical waiting-lists leading to a potential delay in treatment. This study assessed whether a longer time from diagnosis to surgery worsened pathological and survival outcomes in resectable pancreatic ductal adenocarcinoma (PDAC). Methods: A retrospective analysis of patients treated for resectable PDAC. Difference in size between preoperative CT-scan and specimen, pathological features, the rate of vascular and R1 resections as well as recurrence and survival were analyzed depending on the waiting time using a 30-day cut-off. Results: Waiting more than 30 days for surgery was associated with an increase in tumor size on specimen when compared with CT-scan (+3 vs. +1 mm, p = 0.04). T and N status, rate of vascular resection, grading, perineural and lymphovascular infiltration, and R1 rates did not differ between groups, as well as tumor recurrence (48.8% vs. 48.9%, p = 0.5) and survival (31 vs. 29 months, p = 0.7). For PDAC < 20 mm, waiting less than 30 days improved overall survival (p = 0.02). Conclusion: The duration of the surgical waiting-list did not affect pathological features and survival. Delayed surgery was associated with increased cancer size on the specimen. However, surgery should not be delayed for PDACs < 20 mm as this may negatively affect the prognosis.